ANALISIS PERBANDINGAN BIAYA DAN WAKTU PELAKSANAAN KONSTRUKSI GIRDER KOMPOSIT DAN PRECAST BETON (Studi Kasus Pekerjaan Jembatan 2 Ruas Mensalong - Tau Lumbis, Provinsi Kalimantan Utara) (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
Bridges as transportation infrastructure have dominant benefits for traffic movement. Bridge is a general term for construction that is built as a transportation route that crosses rivers, lakes, swamps, ravines or other obstacles. Basically, bridge construction is not only aimed at connecting devices, but also has broad objectives and functions, including; economic function, social function, political function, cultural function, defense and security function. The purpose of writing this thesis is to determine the comparison and efficiency in terms of cost and time of bridge construction using composite girders and precast concrete. From the results of the comparative analysis of the cost and time of composite girder construction and precast concrete on the construction of the 2 Sei Liu Mensalong - Tau Lumbis Bridge, North Kalimantan Province, it was found that the precast concrete girder construction has a value of 8.85% more economical in terms of cost and 68, 06% faster in terms of time. So it can be concluded that precast concrete girder construction is more efficient in terms of cost and time than composite girder construction. As for the maintenance aspect, composite girders also need to pay regular attention to the frame work, anti-rust painting, bolt inspection, and others.